2007
DOI: 10.4161/cc.6.17.4631
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Polymorphism and the Nucleosome Superfamily: A Genealogy

Abstract: Nucleosomes were discovered more than thirty years ago as the basic repeating units of chromatin. Since then, nucleosomes have progressively revealed their taste to come in many appearances, upon either adjunction of other proteins (e.g., a fifth histone or a nonhistone protein, HMG-N), histone substitution for isoforms (histone variants), depletion of one or the two H2A-H2B dimers (sub-nucleosomes), intimate two-particle association, or isomeric structural alterations. The resulting entities, some of them are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 84 publications
2
45
0
Order By: Relevance
“…According to geometrical modeling of the 30 nm chromatin fiber (Lesne and Victor 2006), a short linker size would rather lead to an open well-ordered chromatin secondary structure that would facilitate the sequential action of chromatin regulators associated with Pol II progression, such as the FACT complex (Hartzog, 2003), as well as the action of chromatin modifiers. Recently, reversomes (for reverse nucleosomes, built on a righthanded tetrasome) were proposed to form under the action of a DNA supercoiling wave pushed in front of the RNA polymerase (Lavelle and Prunell 2007). The nucleosome reversome would facilitate transcription elongation by giving the RNA polymerase a lever to break the docking of the H2A-H2B dimers, which otherwise exerts a stringent blocking against transcription in absence of other factors (Bancaud et al 2007).…”
Section: Proof Onlymentioning
confidence: 99%
“…According to geometrical modeling of the 30 nm chromatin fiber (Lesne and Victor 2006), a short linker size would rather lead to an open well-ordered chromatin secondary structure that would facilitate the sequential action of chromatin regulators associated with Pol II progression, such as the FACT complex (Hartzog, 2003), as well as the action of chromatin modifiers. Recently, reversomes (for reverse nucleosomes, built on a righthanded tetrasome) were proposed to form under the action of a DNA supercoiling wave pushed in front of the RNA polymerase (Lavelle and Prunell 2007). The nucleosome reversome would facilitate transcription elongation by giving the RNA polymerase a lever to break the docking of the H2A-H2B dimers, which otherwise exerts a stringent blocking against transcription in absence of other factors (Bancaud et al 2007).…”
Section: Proof Onlymentioning
confidence: 99%
“…However, several papers have challenged the idea of unalterable cylindrical left-handed nucleosomes and have accumulated evidence for the existence of alternative histone/DNA assemblies, some of which being potentially topologically reversed (right-handed) (reviewed in Ref. 44)). Based on topological assays of particles reconstituted on DNA minicircles, Prunell and colleagues provided the first in vitro evidence for the existence of right-handed (H3-H4)2 tetrasomes.…”
Section: Chiral Issuesmentioning
confidence: 99%
“…53) Henikoff and co-workers previously identified half-nucleosomes in interphasic Drosophila centromeres. 54) These tetrameric particles, further called hemisomes, 44) were then proposed to wrap DNA with an opposite helicity in comparison to "canonical" nucleo-somes, as observed from in vivo investigation of yeast centromeres topology. 53) This raised intriguing new questions, such as how centromeric histone variants may be assembled in a right-handed particle, and how/why chromatin would retain negative supercoiling in chromosome arms but positive supercoiling in centromeres.…”
Section: Chiral Issuesmentioning
confidence: 99%
“…Our results were unequivocal. Cross-linking and purification identified a CenH3 tetramer consisting of one molecule each of CenH3, H4, H2A, and H2B (12), referred to as a ''hemisome'' (13). Nuclease protection showed that this particle wraps Ͻ120 bp of DNA, and EM revealed that the particle is small, separated by long linkers, and resists ionic condensation.…”
Section: Cenh3/h4/h2a/h2b Tetramers Form the Core Of Centromeric Nuclmentioning
confidence: 99%
“…It remains to be seen whether hemisomes are the only CenH3 species found at centromeres because we also detected a larger cross-linked species in mitotic cells that might represent a larger particle. Nevertheless, the existence of a stable nucleosome particle that is similar to a half-nucleosome of the type rarely detected in bulk eukaryotic chromatin is notable in being an exception to the octameric structure of the eukaryotic nucleosome that has been the dominant paradigm for more than 30 years (13). An intriguing possibility is that other histone variants assemble into noncanonical nucleosomes, such as the H2AL1/ L2-TH2B-containing particle found in mouse heterochromatin during spermiogenesis (14) and unusual H3 and H2B variants of trypanosomes (15).…”
Section: Cenh3/h4/h2a/h2b Tetramers Form the Core Of Centromeric Nuclmentioning
confidence: 99%